Spheroid-type transthyretin amyloidosis in the gallbladder: A possible histopathological diagnostic clue to prevent overlooking cholecystic latent amyloid deposition - Shojiro Ichimata; Yukiko Hata; Kazuhiro Nomoto; Masahiro Oshima; Yosuke Kato; Naoki Nishida (Elsevier, 2020)
An 83-year-old woman underwent cholecystectomy for acute calculous cholecystitis. Histopathologically, the superficial area of the gallbladder was covered by necrotic tissue, and the deeper wall structure was obscured by marked fibrosis and severe inflammatory-cell infiltration. Many small, amorphous, eosinophilic spheroid bodies with a central cavity were identified in the superficial area. They were confirmed as amyloid deposits as they were positive under Congo red staining and exhibited yellow-green birefringence under polarized light. Amyloid deposition was also identified on the vessels in the deeper fibrous layer. Immunohistochemically, these amyloid deposits were positive for transthyretin antibodies, and CD34-positive cells were focally identified at the center of the deposits. These spheroid-type deposits, thought to originate from the affected vessels, formed a characteristic deposition pattern that can be used as a diagnostic sign indicating latent systemic amyloidosis in the gallbladder with severe degeneration that would otherwise interfere with accurate histopathological identification. As we were unable to find any other reported similar cases, this case report of spheroid-type transthyretin-derived amyloidosis in the gallbladder seems to be the first.